Post-socialism is not dead (re)reading the global in comparative education - Silova, Iveta (International perspectives on education and society ;, 2010)
This volume will provide a comparative account of the meanings and processes of post-socialist transformations in education by exploring recent theories, concepts, and debates on post-socialism and globalization in national, regional, and international contexts.